2022
DOI: 10.1038/s41419-022-04962-y
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 regulated by miR-224-5p modulates macrophage reprogramming and exacerbates osteoarthritis associated synovitis by targeting CD32

Abstract: Emerging evidence has shown an imbalance in M1/M2 macrophage polarization to play an essential role in osteoarthritis (OA) progression. However, the underlying mechanistic basis for this polarization is unknown. RNA sequencing of OA M1-polarized macrophages found highly expressed levels of pentraxin 3 (PTX3), suggesting a role for PTX3 in OA occurrence and development. Herein, PTX3 was found to be increased in the synovium and articular cartilage of OA patients and OA mice. Intra-articular injection of PTX3 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…performed an RNA sequencing of OA M1-polarized macrophages and successfully identified that pentraxin 3 (PTX3) is highly expressed in OA patients. Moreover, PTX3 was upregulated when miR-224-5p was insufficient, which activated the p65/NF-κB pathway to induce M1 macrophage polarization by targeting CD32 ( 53 ). Therefore, blockade of this pathway and PTX3 may alleviate the OA development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…performed an RNA sequencing of OA M1-polarized macrophages and successfully identified that pentraxin 3 (PTX3) is highly expressed in OA patients. Moreover, PTX3 was upregulated when miR-224-5p was insufficient, which activated the p65/NF-κB pathway to induce M1 macrophage polarization by targeting CD32 ( 53 ). Therefore, blockade of this pathway and PTX3 may alleviate the OA development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mechanism research of macrophages has also drawn many researchers' attention. For example, NO was found to induce apoptosis and proinflammatory cytokines secretion, while others reported that it could protect chondrocytes and attenuates macrophagemediated inflammation (49)(50)(51)(52)(53). Therefore, exploring the mechanisms underlying on the macrophage and OA progression.…”
Section: Future Research Trendsmentioning
confidence: 99%
“…Inflammatory reaction exists in synovial tissues, that is, the severity of synovitis is associated with the symptoms of OA and the progress of disease to a large extent. A large number of macrophages with different activation states were observed in the synovium of OA patients at different stages ( Yin J. et al, 2022 ; Jia et al, 2022 ). Among them, M1 phenotype macrophages are the main subgroups of inflammatory cytokines production, cartilage degradation, and osteophyte formation in the OA state, while M2 type macrophages have a protective effect on OA by secreting some anti-inflammatory factors ( Lv et al, 2022 ; Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages can proliferate rapidly in pathological environments and release inflammatory factors, resulting in edema of vascular dilatation tissue and cartilage destruction. [ 47 ] LPS can activate macrophages to produce many inflammatory factors (such as tumor necrosis factor alpha (TNF‐α), interleukin 1 beta (IL‐1β), and interleukin 6 (IL‐6)). DS is a kind of NSAID that can inhibit the production of inflammatory factors primarily by inhibiting COX‐2 activity.…”
Section: Resultsmentioning
confidence: 99%